Bored with boredom? Trait boredom predicts internet addiction through the mediating role of attentional bias toward social networks - Loreta Cannito; Loreta Cannito; Irene Ceccato; Eugenia Annunzi; Alessandro Bortolotti; Eleonora D’Intino; Rocco Palumbo; Claudio D’Addario; Claudio D’Addario; Alberto Di Domenico; Riccardo Palumbo; Riccardo Palumbo (Frontiers in Human Neuroscience, 2023)
Internet addiction is an emerging issue, impacting people’s psychosocial functioning and well-being. However, the prevalence and the mechanisms underlying internet misuse are largely unknown. As with other behavioral addiction disorders, the increase and persistence of internet addiction may be favored by negative affect such as boredom. In this study, we examined the role of boredom susceptibility, as a personality trait, in predicting the risk of internet addiction. Furthermore, we analyzed the attentional mechanisms that may exacerbate dysfunctional internet behaviors. Specifically, we assessed the mediating role of attentional bias toward social media cues on the relation between boredom susceptibility and internet addiction. Sixty-nine young adults were administered a dot-probe task assessing internet-related attentional bias (AB) and questionnaires measuring internet addiction (IAT) and boredom susceptibility (BS-BSSS). Correlation and t-test analyses confirmed that the tendency to experience boredom and selective attention toward social network information was related to internet addiction. Furthermore, the mediation model indicated that AB fully explains the link between BS-BSSS and IAT. The study highlighted the crucial role of selective attentional processing behind internet addiction. The current results are useful for both researchers and clinicians as they suggest that intervention programs for internet addiction should include strategies to cope with dysfunctional cognitive processes.